Analisis analisis minat belajar peserta didik dan implementasi model cycle 5 e pada materi kesetimbangan kimia - Yuyun Ernawati; K. H. Sugiyarto; Antuni Wiyarsi; Jaslin Ikhsan (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to analyze students' learning interests in the application of the 5E cycle model to chemical equilibrium material at SMA Negeri 1 Seyegan. The research design used in this study was pre-experimental with a one-shot case study. The research sample consisted of all class X MIPA 1 students, with a total of 27 students. The sampling technique used was purposive sampling. Data collection techniques are carried out with an eye toward measuring student learning interest. The type of data analysis used is descriptive, calculating the proportion of the overall score at the level of interest in learning. The result of the study is that the level of interest in studying at SMA Negeri 1 Seyegan is in the moderate-high category.